Architecture of a hydroelectrically powered wireless sensor node for underground environmental monitoring. (1st October 2017) - Mecocci, Alessandro; Peruzzi, Giacomo; Pozzebon, Alessandro; Vaccarella, Pietro
Abstract : This study describes a sensor node powered by an energy harvesting method based on the watermill principle. This method is suitable whenever a sensor node has to be deployed in the nearby of an underground water line, such as a drainage system or an aqueduct. The operating scenario for whom this solution has been developed and employed is a wireless sensor network for the monitoring of the environmental conditions of the so‐called 'Bottini' in Siena, Italy. The 'Bottini' is a network of medieval aqueducts dug in the underground of the historic centre of the city, in which water still flows nowadays. Using the proposed energy harvesting system the sensor nodes are able to operate independently, minimising the maintenance and allowing the real‐time monitoring of environmental parameters, thanks, in order to manage the preservation of this ancient site. The entire system is composed of three parts: the power generation system, the data acquisition system and the wireless transmission system. The whole architecture has been tested in the operating scenario, precisely in 'Fontebranda', one of the biggest fountains in the 'Bottini' network.